Assessing the impacts of minimum legal drinking age laws on police-reported violent victimization in Canada from 2009 to 2013. (1st April 2019) - Benny, Claire; Gatley, Jodi M.; Sanches, Marcos; Callaghan, Russell C.
Highlights: This study employs a quasi-experimental design to evaluate drinking age laws. The paper uses a national dataset of police-reported violent victimization events. Men and women gaining the drinking age incur increases in violent victimization. Abstract: Background/aim: Given that alcohol-related victimization is highly prevalent among young adults, the current study aimed to assess the potential impacts of Minimum Legal Drinking Age (MLDA) laws on police-reported violent victimization events among young people. Design: A regression-discontinuity (RD) approach was applied to victimization data from the Canadian Uniform Crime Reporting 2 (UCR2) Incident-based survey from 2009-2013. Participants/cases: All police-reported violent victimization events (females: n = 178, 566; males: n = 156, 803) among youth aged 14–22 years in Canada. Measurements: Violent victimization events, primarily consisting of homicide, physical assault, sexual assault, and robbery. Results: In comparison to youth slightly younger than the drinking age, both males and females slightly older than MLDA had significant and immediate increases in police-reported violent victimization events (females: 13.5%, 95% CI: 7.5%–19.5%, p < 0.001; males: 11.6%, 95% CI: 6.6%–16.7%, p < 0.001). Victimizations occurring in the evening rose sharply immediately after the MLDA by 22.8% (95% CI: 9.9%–35.7%, p = 0.001) for females and 19.3% (95% CI: 11.5%–27.2%, p < 0.001) for males. Increases in violent victimization immediately after MLDA were most prominent in bar/restaurant/open-air settings, with victimizations rising sharply by 44.9% (95% CI: 29.5%–60.2%, p < 0.001) among females and 18.3% (95% CI: 7.7%–29.0%, p = 0.001) among males. Conclusions: Young people gaining minimum legal drinking age incur immediate increases in police-reported violent victimizations, especially those occurring in the evening and at bar/restaurant/open-air settings. Evidence suggests that increasing the MLDA may attenuate patterns of violent victimization in newly restricted age groups.